Funcionalidad familiar y su incidencia en el comportamiento en una niña de 8 años de edad de la Ciudadela Los Girasoles en el cantón Ventanas de la Provincia de Los Ríos - Delgado Andrade, Karem Krisol (2020)
The present case study was carried out with the “Dávila Vera” family, it covers a problem that currently occurs, the family system is made up of father, mother and daughter, the girl is a student of the “10 de Noviembre” Educational Unit that is located in the Canton Ventanas, taking into account that the objective is to detail the incidence of the dysfunctional family in the behavior of the minor. To carry out this case study, numerous strategies were used, to obtain the information it was carried out through an observation guide, a systemic family interview and psychometric tests and after that the results were obtained and after that, the diagnosis was reached. During this case study process, it was possible to show that family dysfunction does intercede in the behavioral development of the minor. Through this study, issues such as family, family functionality, cohesion, adaptability were addressed. Taking into account as an important point the family function and its effect on a minor. For this case, a therapeutic plan based on Family Systemic Therapy techniques was proposed so that the family strengthens the union, communication and optimizes the trust and security of the family.